The Comparative Study of Website-Based SDGs Disclosure by Provincial Governments in Indonesia - Sari, Tiyas Kurnia (Jurnal Akuntansi AKUNESA, 2025)
This study aims to analyse the quality of website-based Sustainable Development Goals (SDGs) disclosure by 38 provincial governments in Indonesia and test the significance of disclosure differences between regions. The research method uses a quantitative approach with content analysis techniques on the disclosure of 17 SDGs items on the official website of the provincial government. Data were analysed using descriptive statistics, Kruskal-Wallis test, and One-way ANOVA to test the differences in disclosure between regions. The results showed significant variation in SDGs disclosure, with Java (92.2%) and Kalimantan (91.8%) showing the highest level of disclosure, while Sulawesi (55.0%) and Papua (55.8%) recorded the lowest level of disclosure. Statistical tests (Kruskal-Wallis H = 17.24, p < 0.05; ANOVA F(4,33) = 6.12, p < 0.05) confirmed significant differences between regions. The most expressed SDGs were SDG 3 (Health and Wellbeing, 97%), SDG 4 (Quality Education, 90%), and SDG 17 (Partnership, 90%), while SDG 10 (Reduced Inequality, 56%) was the lowest. This finding implies the need for standardisation of reporting and strengthening institutional capacity, especially in eastern Indonesia.